Synthesis of Amino Acid Analogues of 5H-Dibenz[b,f]azepine and Evaluation of their Radical Scavenging Activity - H. Vijay Kumar; C. R. Gnanendra; Nagaraja Naik (E-Journal of Chemistry)
A method for the synthesis of tyrosine, phenyl alanine, hydroxy proline and threonine free amino acid analogues of 5H-dibenz[b,f]azepine is proposed. 5H-dibenz[b,f]azepine was prepared by known method. The key intermediate 3-chloro-1-(5H-dibenz[b,f]azepine-5-yl)propan-1-one was obtained by N-acylation of 5H-dibenz[b,f]azepine with 3-chloro propionyl chloride. Further coupling of respective free amino acid to produce 2-(3-(5H-dibenz[b,f]azepine-5-yl)-3-oxopropylamino)3-(4 hydroxyphenyl) propanoic acid, 2-(3-(5H-dibenz[b,f]azepine-5-yl)-3-oxopropylamino)-3-phenyl propanoicacid,1-(3-(5H-dibenz[b,f]azepine-5-yl)-3-oxopropyl)-3-hydroxypyrolidine-2-carboxylic acid and 2-(3-(5H-dibenz[b,f] azepine-yl)-3-oxopropyl amino)-3-hydroxy butanoic acid. The synthesized compounds were evaluated for their potential over 1,1-diphenyl-2-picryl hydrazyl (DPPH) free radical scavenging activity. Butylated hydroxy anisole (BHA) and ascorbic acid (AA) were used as the reference antioxidant compounds and also the comparative study with synthesized compounds was done. Under our experimental conditions tyrosine, hydroxy proline and threonine analogues possess a direct scavenging effect on trapping the stable free radical DPPH. Hydroxy proline analogues showed a significant radical scavenging activity among the synthesized analogues